Muticriteria assesment of possible use of computer games in teaching - Žižović, Mališa R.; Plećić, Katarina G. (Vojnotehnički glasnik / Military Technical Courier, 2017)
In this paper we present a multi-criteria evaluation of several possible approaches to organization of studies. A wider use of modern information technology has led to major changes in traditional education. One of them is the development of serious games in order to simulate real business work environment. The traditional passive education approach trains people for some narrow procedures, and then evaluates them based on their memories of what they have been told. Even when students have successfully mastered facts and procedures, their behavior in real life situations remains uncertain. Games are trying to solve this problem, motivate and promote learning. Their interactive aspect leads to high involvement of participants in game activities, so they no longer have the sole purpose of entertainment, but become a serious learning tool. The possibility to provide entertainment and educational component separates these games from classical, fun games. Also, participants are not passive players. Their decisions and actions directly affect the flow of the game, leading to good or bad results. To evaluate game application in classroom, a multicriteria analysis was used. It was used for the assessment of possible study forms in order to use benefits of information technology for modernizing and improving teaching and learning processes. The evaluation was made by observing four alternatives, as well as six criteria. The aim of this paper was to make these applications more effective where needed and to indicate apossibility to use them elsewhere.
Keywords: multi-criteria analysis; criteria; weights of criteria; games; simulation